The role of physical activity in prevention of neurodegenerative diseases via irisin synthesis – a contemporary review - Grzyb, Izabela; Łysynkiewicz, Katarzyna; Szewczyk, Jan; Wątek, Zuzanna; Smolińska, Alicja (Journal of Education, Health and Sport, 2026)
Background: Neurodegenerative diseases pose as a growing challenge due to population aging and the lack of causal therapies. Shared pathological mechanisms include oxidative stress, mitochondrial dysfunction, and chronic neuroinflammation. Regular physical activity shows neuroprotective effects, and irisin—an exercise-induced myokine generated by proteolytic cleavage of FNDC5 under PGC-1α control—may be an important mediator of the muscle–brain axis. Aim: To present the current state of knowledge on irisin, with particular emphasis on its role in the pathogenesis, diagnosis, and potential treatment of neurodegenerative diseases. Material and methods: This narrative review summarizes available evidence on the biological properties of irisin, its proposed mechanisms of action and its effects on energy metabolism, inflammation, oxidative stress, and neuroplasticity in the context of NDDs. Results: Experimental studies indicate that irisin increases hippocampal BDNF expression, promotes neurogenesis and synaptic plasticity, and reduces neuronal apoptosis. In Alzheimer’s disease models, FNDC5/irisin levels were reduced in the hippocampus and cerebrospinal fluid, whereas increasing FNDC5/irisin improved memory and attenuated amyloid-related pathology. In Parkinson’s disease models, irisin reduced α-synuclein aggregation, protected dopaminergic neurons, and improved motor performance. In ALS, irisin has been proposed to modulate oxidative stress and neuroinflammation through NRF2 activation and NF-κB inhibition, although clinical evidence remains limited. Conclusions: Irisin is a promising biomarker and potential therapeutic target in neurodegenerative diseases. Despite encouraging preclinical results, clinical translation requires well-designed human studies. At present, regular physical activity remains the most practical strategy to modulate endogenous irisin levels and may support prevention and management of NDDs.